Simple and Mixed Reverse Micelles as Potential Bioreactors for Enzymatic Synthesis of Alkyl Glycosides – Environmentally Friendly Surfactants - Irina Mladenoska (Food Technology and Biotechnology, 2012)
Two types of microemulsion reaction systems: simple and mixed reverse micelles have been investigated as potential bioreactors for a transglycosylation reaction catalyzed by three microbial β-galactosidases: fungal Aspergillus oryzae, yeast Kluyveromyces marxianus and bacterial Escherichia coli β-galactosidase. Several issues such as: the effect of the degree of hydration on the total enzyme activity, the enzyme selectivity towards glycon donors, the interphase quality of simple and mixed micelles and the effect of addition of nonionic cosurfactants on the enzyme activity were all discussed. Both p-nitrophenyl-β-D-galactoside and p-nitrophenyl-β-D-glucoside were used as activated substrates. The total activity of all three examined enzymes showed to be strongly dependent on the degree of hydration of reverse micellar systems and had the highest values at the degree of hydration close to the level of saturation. The highest activity that the A. oryzae β-galactosidase had in simple micelles per mass of protein was 1.8 mmol/(min·mg). The ratio of β-galactosidase and β-glucosidase activities had values above 1 for all the enzymes entrapped in simple micelles, which means that their selectivity towards the p-nitrophenyl-β-galactoside as a glycon donor was strict and higher than that towards the p-nitrophenyl-β-glucoside. This ratio for the A. oryzae β-galactosidase was 1.68. The addition of nonionic cosurfactants had a positive effect on the enzyme activity. Thus, the total activity of A. oryzae β-galactosidase in dioctyl sodium sulfosuccinate/polyethylene glycol (AOT/PEG) mixed micelles with a mass ratio ζ(AOT, PEG)=1 was 1.5 times higher and in AOT/Tween mixed micelles with a mass ratio ζ(AOT, Tween)=0.033 it was even more than 3.5 times higher than the activity of enzyme entrapped in simple micellar reactor. The latter activity was even 4.22 times higher than that of A. oryzae β-galactosidase used as a crude enzyme preparation.